2021
DOI: 10.1016/j.mjafi.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and clinical predictors of mortality in hospitalised patients of COVID 19 : An Indian study

Abstract: Background The rapid spread of the coronavirus disease 2019 (COVID-19) with high mortality rate necessitates disease characterization and accurate prognostication for prompt clinical decision-making. The aim of this study is to study clinical characteristics and predictors of mortality in hospitalized patients with COVID-19 in India. Methods Retrospective cohort study was conducted in a tertiary care hospital in northern India. All consecutive confirmed hospitalized COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Notably, the demographic, clinical, and comorbidity profile of the patients analyzed in this study was similar to that observed in other studies on hospitalized patients with COVID-19 [2,27,28]. International and Brazilian studies have shown that the presence of comorbidities such as hypertension, diabetes mellitus, and obesity increases the risk of death among patients with COVID-19 [1,2]. In this study, the most common comorbidity was hypertension, followed by diabetes mellitus, obesity, and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Notably, the demographic, clinical, and comorbidity profile of the patients analyzed in this study was similar to that observed in other studies on hospitalized patients with COVID-19 [2,27,28]. International and Brazilian studies have shown that the presence of comorbidities such as hypertension, diabetes mellitus, and obesity increases the risk of death among patients with COVID-19 [1,2]. In this study, the most common comorbidity was hypertension, followed by diabetes mellitus, obesity, and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 86%
“…Notable symptoms include cough, sore throat, runny nose, nasal congestion, anosmia, ageusia, diarrhea, abdominal pain, fever, chills, headache, and myalgia. The inflammatory process that develops in the early stages of the disease, can leads to progressive worsening of respiratory symptoms, which can progress to pneumonia with dyspnea, fatigue, and hypoxemia [2].…”
Section: Introductionmentioning
confidence: 99%
“…16 Diabetes causes an inhibition in neutrophil chemotaxis, phagocytosis, and intracellular destruction of microbes, thus offering efficient virus entry and decreased viral clearance. 17 In our study, patients above 40 years of age had 1.3 times higher adjusted odds of dying than the younger patients, which increased to 2.1 time with advanced age ≥ 60 year. Advanced age, especially ≥ 60 year, is an established independent risk factor for dying in COVID-19 patients, as shown in various studies across multiple countries since the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 43%
“…16 Diabetes causes an inhibition in neutrophil chemotaxis, phagocytosis, and intracellular destruction of microbes, thus offering efficient virus entry and decreased viral clearance. 17…”
Section: Discussionmentioning
confidence: 99%
“…In India, age, dyspnea, and the presence of comorbid diseases such as malignancy and DM were significantly associated with increased mortality. 27 In the nearby regions, age and some biochemical and vital measures were associated with mortality in United Arab Emirates. 16 End-stage renal disease was also observed as a significant predictor of mortality among patients with COVID-19 in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%